A Study of the Main Drivers that Influence Work Turnover and Retention of Chinese Post-90s Employees - Kang, Zixuan (2020)
With the fierce competition in workplace, more and more organisations try to seek ways to retain talents, since human resource has been increasingly recognised as an important element in workplace. Whereas nowadays there is an increasing number of post 90s employees finding jobs in organisations, and the turnover rates has become higher and higher. Thus, this is the first reason of this dissertation, which is to find out the major factors that cause turnover intentions of post 90s employees. Besides, there are not many literatures about the turnover intentions of Chinese post 90s employees, so another reason of this study is to fill in the gap in literatures. As for this research, it is mainly studied from four perspectives: job satisfaction (salary satisfaction, training and promotion), corporate culture, educational level and marital status.